Popular opinion in totalitarian regimes : fascism, nazism, communism - Corner, Paul 1944- Hrsg (Oxford Univ. Press, 2009)
Popular opinion in Russia under pre-war Stalinism / Sheila Fitzpatrick -- Consensus, coercion and popular opinion in the Third Reich: some reflections / Ian Kershaw -- Liberation from autonomy: mapping self-understandings in Stalin's time / Jochen Hellbeck -- Beyond binaries: popular opinion in Stalinism / Jan Plamper -- Popular opinion in Nazi Germany as a factor in the policy of the 'solution of the Jewish Question': the Nuremberg Laws and the Reichskristallnacht / Otto Dov Kulka -- Popular opinion in Nazi Germany: mobilization, experience, perceptions: the view from the Württemberg countryside / Jill Stephenson -- Fascist Italy in the 1930s: popular opinion in the provinces / Paul Corner -- Poland: the silence of those deprived of voice / Marcin Kula -- Consent in the Communist GDR or how to interpret Lion Feuchtwanger's blindness in Moscow 1937 / Martin Sabrow -- Demography, opportunity or ideological conversion? Reflections on the role of the 'Second Hitler Youth generation', or '1929ers', in the GDR / Mary Fulbrook -- Tacit minimal consensus: the always precarious East German dictatorship / Thomas Lindenberger